Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Employee Engagement Sebagai Mediasi Di Pt Xyz - Kurniasari, Febria Nurindah; Kassmawati, Yuni (Pascasarjana STIE Amkop Makassar, 2025)
This study aims to analyze the relationship and the role of employee engagement in mediation the influence of motivation and work environment on employee performance. The population of this study consisted of all employees of PT XYZ in Jakarta, with a sample of 128 respondents selected using nonprobability sampling technique. Data were collected through questionnaires distributed both directly and online. The analysis method used is Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The results showed that work motivation and work environment have a significant effect on employee performance. In addition, work motivation and work environment also have a significant effect on employee engagement. Employee engagement is proven to have a positive influence on employee performance, and acts as a mediator variable in the relationship between work motivation and work environment on employee performance. These findings provide important implications for the management of PT XYZ in designing policies to improve employee performance through increasing motivation and a supportive work environment, as well as strengthening employee engagement.Keywords: Work Motivation, Work Environment, Employee Performance, Employee Engagement